THE IMPORTANCE AND NEED FOR INNOVATIVE DEVELOPMENT OF MOUNTAIN TOURISM IN UZBEKISTAN - Khidirov, Alimardon Dagarovich (THE INNOVATION ECONOMY, 2026)
The mountains of Uzbekistan are first included in the Pamir-Aloy and then in the Aloy-Hissar mountain range, which is a continuation of the Aloy mountain range, and then splits into the Turkestan, Zarafshan and Hissar ranges in the west from the Mastchoh junction, which is considered a continuation of the Aloy mountain range. This range extends from the Mastchoh pass to the city of Jizzakh in the meridional direction for 320 km, and its height decreases from east to west. Due to the beautiful and fascinating nature of the mountains of Uzbekistan, it is considered a region rich in international tourist attractions. Therefore, the construction of tourist attractions in these regions, taking into account nature, and the innovative development of international mountain tourism are of significant scientific and practical importance. The need to build resort and tourist facilities in the mountains is associated with the aggravation of the ecological situation in the plains of the republic and environmental pollution in large cities. In the article, the author scientifically substantiates the importance and necessity of innovative development of mountain tourism in Uzbekistan.